Experimental Human Cell and Tissue Models of Pemphigus - Gerda van der Wier; Hendri H. Pas; Marcel F. Jonkman (Hindawi Limited, 2010)
Pemphigus is a chronic mucocutaneous autoimmune bullous disease that is characterized by loss of cell-cell contact in skin and/or mucous membranes. Past research has successfully identified desmosomes as immunological targets and has demonstrated that acantholysis is initiated through direct binding of IgG. The exact mechanisms of acantholysis, however, are still missing. Experimental model systems have contributed considerably to today's knowledge and are still a favourite tool of research. In this paper we will describe to what extent human cell and tissue models represent the in vivo situation, for example, organ cultures of human skin, keratinocyte cultures, and human skin grafted on mice and, furthermore, how suitable they are to study the pathogenesis of pemphigus. Organ cultures closely mimic the architecture of the epidermis but are less suitable to answer posed biochemical questions. Cultured keratinocyte monolayers are convenient in this respect, but their desmosomal make-up in terms of adhesion molecules does not exactly reflect the in vivo situation. Reconstituted skin is a relatively new model that approaches organ culture. In models of human skin grafted on mice, acantholysis can be studied in actual human skin but now with all the advantages of an animal model.